Juquitiba na modernidade: uma análise da condição socioespacial - Marcelino, Denise de Camargo (Universidade Federal de São Carlos, 2018)
The objective of this study was to identify the process of expansion of the urban way of life that induces socio-spatial segregation, and how an economic and social formation of the place is resistant and present: a temporality parallel to that of global time, which is still part of modernity. The analysis used the concept of place better describe this temporality, starting from the scale of the neighborhood inserted in the municipality. The neighborhood, containing a specific socio-spatial formation, which, not totally achieved by the urbanization of life, is a testimony of a differential temporality that is defended modernity. The importance of place becomes essential to move transformations and give individuals the strength to transform their world, allowing the coexistence of contrasting times in space.
Juquitiba in modernity: an analysis of the socio-spatial condition
Keywords: Modernidade; Temporalidade; Lugar; Modernity; Temporality; Place; CIENCIAS HUMANAS::GEOGRAFIA::GEOGRAFIA HUMANA